Sistem Informasi Pengadaan Pupuk Dan Fungisida Berbasis Web (Studi Kasus: PT. Hutahaean, Pekanbaru - Riau) - Jeperson Hutahaean; Rolly Yesputra (RJOCS (Riau Journal of Computer Science), 2018)
As a company engaged in agribusiness one of the operational activities is the procurement of fertilizers and fungiciders that are directly related to the fullfilment  of needs in oil palm platantations PT. Hutahaean in Dalu-dalu. For data processing and data reportingevry fertilizer and fungiside procurement has been done manuallu by using computer. As the advances in computer technology have made an appropriate change impact on several aspects,  so worthy of being the media of information technology in the business world to get the ease  and development of technologi progress itself. Research begins by collecting the required data with several methods of interviews, field studies, literature studies and direct observation of the system ceated, the system created using the programming language php. The research aims to facilitate the management of PT. Hutahaean in seeing the stock of goods from the manual into a computerized system using a  web-based system, this system is closely related to computer media, hope this system can produce information easily, quickly and accurately. Fertilizer and fungicide procurement information system is designed using mysql as storage media, php as scrip and web to access. The outline of the information system carried out can run as it should but need development and evalution.